Analisis Biaya Mesin Combine Harvester pada Usahatani Padi di Desa Mattirowalie Kecamatan Tanete Riaja Kabupaten Barru - risna risna (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2022)
Cost Analysis of Combine Harvester Machine on Rice Farming in Mattirowalie Village, Tanete Riaja District, Barru Regency. This research was conducted in Mattirowalie Village, Tanete Riaja District, Barru Regency. Determination of the location is determined based on “purposive sampling” on the basis of the consideration that there are farmers who already have combine harvester machines and farmers who use combine harvester machines. This study aims to determine the cost analysis of combine harvester machines in rice farming in Mattirowalie Village, Tanete Riaja District, Barru Regency. Informants in this study were 1 rice farmer who owns and uses combine harvester technology. The data analysis used is quantitative data analysis. The results showed that the area of land harvested using a combine harvester machine in Mattirowalie Village, Tanete Riaja District, Barru Regency was about 85.71 hectares. The potential for grain harvested using a harvesting machine is about 6000 sacks or the equivalent of 660,000 kg of unhulled rice. The total grain produced by the machine owner is 600 sacks based on the profit-sharing system agreed by the machine owner and the tenant farmer, which is 1: 10, meaning that from 10 sacks, the machine owner gets 1 sack. The total costs incurred starting from fixed costs consisting of depreciation costs, tax costs, and warehouse/garage costs are Rp. 63,770,783. While the total variable costs are Rp. 121,894,718 and total revenue reached Rp. 270,000,000. so that the income from the combine harvester machine in each year is Rp. 84,334,500.